Self-care use patterns in the UK, US, Australia, and Japan: a multinational web-based survey - Sujeong Mun; Jeong-Hwan Park; Seung-Min Baek; Minhee Lee; Sun-Mi Choi; Sanghun Lee (Integrative Medicine Research)
Background: The trend toward patient- or consumer-centered healthcare has been accelerated by advances in technology, consumer empowerment, and a shift from infectious to chronic diseases. The purpose of this study was to examine the growing self-care market by analyzing self-care patterns. Methods: We conducted a cross-sectional, web-based survey involving adults from nine major cities in the UK, the USA, Australia, and Japan. This study examined the extent and frequency of self-care, self-care expenditure, sources of self-care information, and reasons for self-care in each country. Results: The results showed that the prevalence of self-care was highest in Japan (54.9%), followed by the UK (43.1%), the USA (42.5%), and Australia (40.4%). The primary reason for practicing self-care was “to manage my healthcare myself” (cited by 45.7%, 59.5%, 49.2%, and 4.1% of participants in Australia, Japan, the UK, and the USA, respectively). Significant linear associations were observed between age and the prevalence of self-care in all countries (p < 0.05), indicating that self-care prevalence decreased with age in the UK, the USA, and Australia, and increased with age in Japan. The frequency with which self-care was practiced was positively correlated with age in the USA (p < 0.05), Australia (p < 0.01), and Japan (p < 0.05). In addition to acquaintances, internet search engines and information obtained from pharmacies were considered reliable and widely used sources of self-care information. Conclusion: When developing self-care products or services, healthcare providers and policymakers should consider self-care patterns.